Analisis Kecerdasan Emosional dan Kinerja Guru Pendidikan Agama Islam (PAI) di SD Negeri 191 Kotanopan, Sumatera Utara - Parinduri, Khoirunnisa; Trisno, Bambang; Arsya, Fajriyani; Dewi, Puti Andam (STAI Denpasar Bali, 2024)
This research intends to analyze the emotional intellect and ability of Islamic education teachers at SD Negara 191 Kotanopan and to analyze the ability of Islamic education teachers at SD Negara 191 Kotanopan. This research uses descriptive research type. There are also methods of collecting information using observation, question and answer and selection. The result of this research is that the emotional intellect of Islamic education teachers in SD Negara 191 Kotanopan is not good. This is evidenced by the teacher's lack of coolness in dealing with students, the teacher does not often share encouragement with students, and in telling students to pick up dirt the teacher does not prove exemplary in the form of participating and picking up dirt. The ability of Islamic religious education (PAI) teachers at SD Negara 191 Kotanopan is not good. This is evidenced by teachers who arrive at school late, teachers after sharing learning go to eat and do not monitor teaching participants in the learning method, teachers who do not monitor teaching participants when cleaning, teachers only use preaching procedures with constant methods and lack of passion for exploring learning methods, teachers who do not organize category space during the learning method.